Physical fitness, psychological characteristics, and game performance in youth male soccer players of different levels of competition - Koudellis, M.; Tsouloupas, C.; Christou, M.; Aphamis, G.; Bogdanis, G. C.; Giannaki, C. D. (International Journal of Performance Analysis in Sport, 2025)
This cross-sectional study examined the differences and associations regarding physical fitness, psychological characteristics, and game performance between elite (n = 64), sub-elite (n = 82), and non-elite (n = 97) youth male soccer players aged 16.2 ± 0.5 years. Physical fitness parameters were assessed using field tests, psychological characteristics were evaluated using validated questionnaires and technical - tactical data were recorded during a competitive soccer match using a multicamera, semiautomatic optical tracking system. Elite players demonstrated superior performance in cardiorespiratory fitness, countermovement jump (CMJ), 10 m sprint, and agility, compared to the sub-elite and the non-elite players. Also, the elite and sub-elite players had faster 40 m sprints than the non-elite players. Game performance was significantly better in the elite group than the other groups and was associated with coping with the adversity and coachability, tension-anxiety, anger-hostility, and fatigue-inertia subscales. Among the physical fitness parameters examined, only agility and CMJ were associated with game performance. In conclusion, elite youth soccer players performed significantly better in various physical fitness and psychological parameters and demonstrated a higher game performance indicator score compared to their sub-elite and non-elite peers. Results suggested that physical fitness and psychological parameters are essential predictors of game performance.